Extreme load analysis of flexible wave energy converters utilising nonlocal continuum damage mechanics - DEEPAK GEORGE (Applied Ocean Research, 2024)
In recent years, there has been a notable increase in interest towards Flexible Wave Energy Converters (FlexWECs). These flexible energy harvesters solve structural design challenges faced by rigid-body WECs by responding to external loading by changing shapes. Typically, the structures are made from rubber-like materials which pose few challenges from a material modelling point of view. Firstly, the material is in the finite strain regime requiring a hyperelastic modelling approach, but more critically the material response is expected to change during the operational lifetime. There is softening from both time-dependent viscoelasticity and micro-void growth caused by fatigue loading. The goal of this paper is to understand the latter mechanism and how it manifests within a membrane. To account for this damage accumulation, the gradient-enhanced nonlocal damage model is coupled to a hyperelastic Neo-Hookean constitutive law. The framework has been implemented in the commercial finite element software ABAQUS by exploiting its fully coupled thermo-mechanical formulation. A parametric study is performed on two FlexWEC archetypes: a submerged pressure differential and a floating bulge wave attenuator. The performance evaluation of these devices is carried out by analysing the evolution of the pressure–volume relation and pressure-stretch relation, respectively. The results show that the nonlocal aspects of damage in the pressure differential FlexWECs are small due to membrane action, but the saturation of damage does affect the pressure–volume function of each membrane. However, in the case of attenuator, the damage regularisation plays a crucial role in its behaviour due to the steep stress gradient from the crest of the wave. The outcomes from these analyses suggest FlexWEC design is advantageous from a fatigue loading perspective as it always reaches an equilibrium state which minimises the stress-differential, reducing the likelihood of localised crack growth.